Long-term Western diet intake leads to dysregulated bile acid signaling and dermatitis with Th2 and Th17 pathway features in mice. Issue 1 (July 2019) - Jena, Prasant Kumar; Sheng, Lili; Mcneil, Kyle; Chau, Thinh Q.; Yu, Sebastian; Kiuru, Maija; Fung, Maxwell A.; Hwang, Samuel T.; Wan, Yu-Jui Yvonne
Highlights: Western diet (WD) facilitated the development of dermatitis in C57BL/6 mice. WD-exacerbated dermatitis is sex-dependent with higher incidence in female mice. Reduced TGR5 and S1PR2 signaling was found in the dermis of WD-fed mice. WD-induced lesional skin has activated TGR5 and S1PR2 signaling. Cholestyramine supplementation reduced dermatitis in WD-fed mice. Abstract: Background: Dietary interventions are implicated in the development of atopic dermatitis, psoriasis, and acne. Objective: To investigate the effect of diet and the bile acid (BA) receptors, such as TGR5 (Takeda G protein receptor 5) and S1PR2 (sphingosine-1-phosphate receptor 2) in the development of dermatitis. Methods: C57BL/6 mice were fed a control diet (CD) or Western diet (WD) since weaning until they were 10 months old followed by analyzing histology, gene expression, and BA profiling. Results: Mice developed dermatitis as they aged and the incidence was higher in females than males. Additionally, WD intake substantially increased the incidence of dermatitis. Cutaneous antimicrobial peptide genes S100A8, S100A9, and Defb4 were reduced in WD-fed mice, but increased when mice developed skin lesions. In addition, Tgr5 and TGR5-regulated Dio2 and Nos3 were reduced in WD intake but induced in dermatitic lesions. Trpa1 and Trpv1, which mediate itch, were also increased in dermatitic lesions. The expression of S1pr2 and genes encoding sphingosine kinases, S1P phosphatases, binding protein, and transporter were all reduced by WD intake but elevated in dermatitic lesions. Furthermore, dermatitis development increased total cutaneous BA with an altered profile, which may change TGR5 and S1PR2 activity. Moreover, supplementation with BA sequestrant cholestyramine reduced epidermal thickening as well as cutaneous inflammatory cytokines. Conclusion: In summary, activation of TGR5 and S1PR2, which regulate itch, keratinocyte proliferation, metabolism, and inflammation, may contribute to WD-exacerbated dermatitis with Th2 and Th17 features. In addition, elevated total BA play a significant role in inducing dermatitis and cutaneous inflammation.